Formal and Social Enforcement in Response to Individual Versus Corporate Transgressions. Issue 4 (December 2016) - Haran, Uriel; Teichman, Doron; Feldman, Yuval
Abstract : Social enforcement of norms governing appropriate business practices, through online and social networks, is regarded as an effective alternative to formal, state‐sponsored enforcement. However, recent research finds that such norms are interpreted differently when applied to individual actors than when applied to corporations. This article finds that this difference transcends to enforcement, and that willingness to actively respond to a transgression depends on both the transgressor's identity and the type of violation. Three studies found that people are reluctant to substitute social enforcement for state‐sponsored action, and that the preference for formal over social action was generally more pronounced when the target of the action was an individual than when the action targeted a corporation. Furthermore, individuals were judged more severely for intentional harms, whereas corporations received higher levels of critique for violations caused by negligent behavior. Our findings suggest that the state may need to exercise caution in outsourcing norm enforcement in commercial relationships.